2018
DOI: 10.1101/357665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of chronic spinal cord injury on relationships among ion channel and receptor mRNAs in mouse lumbar spinal cord

Abstract: Spinal cord injury (SCI) causes widespread changes in gene expression of the spinal cord, even in the undamaged spinal cord below the level of the lesion. Less is known about changes in the correlated expression of genes after SCI. We investigated gene co-expression networks among voltage-gated ion channel and neurotransmitter receptor mRNA levels using quantitative RT-PCR in longitudinal slices of the mouse lumbar spinal cord in control and chronic SCI animals. These longitudinal slices were made from the ven… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(67 reference statements)
2
4
0
Order By: Relevance
“…We investigated this hypothesis using simplified biophysical models of pacemaker neurons that use a single sensor of calcium concentration to control ion channel expression homeostatically. Previous work showed that this class of self-tuning models recapitulates experimental observations such a correlations in ion channel density ( Schulz et al, 2006, 2007 ; Temporal et al, 2014 ; Garcia et al, 2018 ; O’Leary et al, 2013, 2014 ). Furthermore, these models provide robustness to some forms of perturbations in membrane conductances, but can be sensitive to other perturbations like channel deletions ( O’Leary et al, 2014 ).…”
Section: Introductionsupporting
confidence: 58%
“…We investigated this hypothesis using simplified biophysical models of pacemaker neurons that use a single sensor of calcium concentration to control ion channel expression homeostatically. Previous work showed that this class of self-tuning models recapitulates experimental observations such a correlations in ion channel density ( Schulz et al, 2006, 2007 ; Temporal et al, 2014 ; Garcia et al, 2018 ; O’Leary et al, 2013, 2014 ). Furthermore, these models provide robustness to some forms of perturbations in membrane conductances, but can be sensitive to other perturbations like channel deletions ( O’Leary et al, 2014 ).…”
Section: Introductionsupporting
confidence: 58%
“…Our model assumes a single sensor of calcium concentration to control expression of multiple ion channels simultaneously, a so called master regulation scheme. Previous work showed that this class of self-tuning models recapitulates experimental observations such a correlated variability in ion channel density and compensation for changes in circuit activity [17][18][19][20][21][22] .…”
supporting
confidence: 54%
“…In our previous work, we designed or modified and independently validated qPCR primers for use in absolute quantitation of mRNA copy number for all of the genes of interest in this study. These primer sets are previously published, and standard curves generated and used as described in our previous work (Garcia et al 2014, 2018). Briefly, qPCR reactions were carried out using SYBR mastermix (BioRad) according to the manufacturer’s instructions, and consisted of primers at final concentrations of 2.5 μM.…”
Section: Methodsmentioning
confidence: 99%